2021
DOI: 10.1186/s40645-020-00397-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the contribution of tropical cyclone seeds to changes in tropical cyclone frequency due to global warming in high-resolution multi-model ensemble simulations

Abstract: Previous projections of the frequency of tropical cyclone genesis due to global warming, even in terms of sign of the change, depends on the chosen model simulation. Here, we systematically examine projected changes in tropical cyclones using six global atmospheric models with medium-to-high horizontal resolutions included in the sixth phase of the Coupled Model Intercomparison Project/High-Resolution Model Intercomparison Project. Changes in the frequency of tropical cyclone genesis could be broken down into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 59 publications
2
28
3
Order By: Relevance
“…Emanuel et al (2013) identifies three thermodynamic variables useful to understand the formation of TCs: 1) the presence of moist convection; 2) mid-tropospheric humidity and 3) Potential Intensity (PI). We have focused so far on the last two variables, part of GPI, and their role in the conversion of TC seeds; our findings are supportive of the conclusions in Vecchi et al (2019) and Yamada et al (2021). The role of moist convection may not be revealed by GPI, but can be investigated by Watson et al (2017) for the same model.…”
Section: E Gpi Terms and Their Control On The Climatology Of Tcs In Each Basinsupporting
confidence: 81%
“…Emanuel et al (2013) identifies three thermodynamic variables useful to understand the formation of TCs: 1) the presence of moist convection; 2) mid-tropospheric humidity and 3) Potential Intensity (PI). We have focused so far on the last two variables, part of GPI, and their role in the conversion of TC seeds; our findings are supportive of the conclusions in Vecchi et al (2019) and Yamada et al (2021). The role of moist convection may not be revealed by GPI, but can be investigated by Watson et al (2017) for the same model.…”
Section: E Gpi Terms and Their Control On The Climatology Of Tcs In Each Basinsupporting
confidence: 81%
“…This is somewhat contrary to previous studies (Hsieh et al, 2020;Vecchi et al, 2019;Yamada et al, 2021) which revealed that the change in TC seed frequency has a large impact on TC frequency in the future warmer climate. However, Yamada et al (2021) noted in their multimodel analysis that survival rate is also influential in some models, and Duvel (2021) showed that seasonal and interannual variations in TC frequency over the North Atlantic is more attributed to survival rate than to the number of vortices from Africa. It seems that definitions or tracking algorithms of TC seeds cannot account for this contradiction because they are different even among the aforementioned studies with similar conclusions.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
“…Previous studies have shown that the probability and seeds framework could help explain diverging responses of TC frequency to radiative climate forcing induced by greenhouse gases ( 3 , 11 , 21 , 22 ). Here we test and validate that the seeds-probability framework also works in a different scenario: climatological variations driven by the annual cycle radiative forcing.…”
Section: Summary and Discussionmentioning
confidence: 99%